2022
DOI: 10.1002/jaba.902
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of stereotypy: Applicability of the behavioral subtyping model

Abstract: Recent research on automatically reinforced self‐injurious behavior (ASIB) has identified specific patterns of responding in functional analyses that correlate with intervention efficacy (Hagopian et al., 2015; Hagopian et al., 2017). Whereas research by Hagopian et al. (2015, 2017) points to an important development in the assessment and treatment of ASIB, it is unclear if the applicability extends to automatically reinforced noninjurious behaviors, including stereotypy. Therefore, the current study replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…An additional 14 applications targeted other automatically maintained behavior (e.g., perseverations, spitting, and stereotypy). Although there is currently no basis for applying the subtyping model to behavior other than SIB and only one study that applied subtyping parameters to stereotypy (Wunderlich et al, 2022), an exploratory analysis of the relation between the level of differentiation of challenging behavior in the functional analysis and CSA outcomes for non-SIB automatically maintained behavior was examined. This was accomplished by using the same 62.5% cutoff value for distinguishing between automatically maintained SIB Subtypes 1 and 2.…”
Section: Csa Outcomes For Applications Targeting Automatically Mainta...mentioning
confidence: 99%
“…An additional 14 applications targeted other automatically maintained behavior (e.g., perseverations, spitting, and stereotypy). Although there is currently no basis for applying the subtyping model to behavior other than SIB and only one study that applied subtyping parameters to stereotypy (Wunderlich et al, 2022), an exploratory analysis of the relation between the level of differentiation of challenging behavior in the functional analysis and CSA outcomes for non-SIB automatically maintained behavior was examined. This was accomplished by using the same 62.5% cutoff value for distinguishing between automatically maintained SIB Subtypes 1 and 2.…”
Section: Csa Outcomes For Applications Targeting Automatically Mainta...mentioning
confidence: 99%
“…Namely, Hagopian and colleagues found that clients who engaged in the highest rates of self-injury during the alone condition and the lowest rates in the play condition (subtype 1) were more likely to benefit from reinforcement alone than those who engaged in self injury across all conditions (subtype 2; Hagopian et al, 2017Hagopian et al, , 2018. This subtype categorization, however, may not hold for other topographies (e.g., stereotypy, Wunderlich et al, 2022). Further, responding across all conditions within the traditional multi-element design (undifferentiated responding; subtype 2) may alternatively suggest carry over effects or lack of discrimination among conditions, warranting additional analysis prior to determining an automatic function (Hagopian et al, 1997;Vollmer et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Most published articles on the treatment of vocal stereotypy have shown that this behavior often persists in the absence of social consequences, otherwise known as being maintained by automatic reinforcement (Vollmer, 1994). Nonetheless, practitioners should implement experimental functional analyses of vocal stereotypy to confirm function and inform treatment (Rapp & Lanovaz, 2016; Wunderlich et al, 2022). Several effective treatments have been used to decrease automatically reinforced vocal stereotypy including providing noncontingent access to matched or competing auditory stimuli (e.g., Lanovaz et al, 2012) as well as access to reinforcers for the absence of stereotypy (Taylor et al, 2005).…”
mentioning
confidence: 99%